2004
DOI: 10.4049/jimmunol.172.9.5149
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TGF-β Induces a Regulatory Phenotype in CD4+CD25− T Cells through Foxp3 Induction and Down-Regulation of Smad7

Abstract: CD4+CD25+ regulatory cells are a subpopulation of T lymphocytes of thymic origin. However, recent data suggest an alternative commitment of regulatory T cells in the periphery, although the precise mechanism is unknown. In the present work, we demonstrate that TGF-β is able to induce Foxp3 expression and subsequently a regulatory phenotype in CD4+CD25− peripheral murine T cells. Similarly, TGF-β induced Foxp3 in human CD4+CD25− T cells. Moreover, we show that the inhibitory Smad7 protein that is normally induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
741
6
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,038 publications
(798 citation statements)
references
References 16 publications
23
741
6
10
Order By: Relevance
“…Studies have reported that TGF-has the ability to induce CD4 + CD25 -cells to become CD4 + CD25 + Tregs in vitro [52,53], and TGF-can induce FoxP3 expression in iTregs [54,55]. Additionally, other studies have clearly demonstrated that the suppressive capacity of FoxP3 + Tregs in vivo is via a TGF--dependent mechanism [56,57].…”
Section: Transforming Growth Factor-mentioning
confidence: 99%
“…Studies have reported that TGF-has the ability to induce CD4 + CD25 -cells to become CD4 + CD25 + Tregs in vitro [52,53], and TGF-can induce FoxP3 expression in iTregs [54,55]. Additionally, other studies have clearly demonstrated that the suppressive capacity of FoxP3 + Tregs in vivo is via a TGF--dependent mechanism [56,57].…”
Section: Transforming Growth Factor-mentioning
confidence: 99%
“…As mentioned earlier, the initial studies indicating that FOXP3 was exclusively expressed in human nTreg [9,10] have been disputed by recent works that identified transient FOXP3 expression in activated human CD4 + CD25 -T effector (Teff) cells in the presence or absence of TGF-b [9,[11][12][13][14][15][16][17]. Notably, the resulting FOXP3-expressing T cells can either exert suppressive functions [9,11,13,15,18] or not [12,14,[16][17][18].…”
Section: Foxp3 Expression In T Cellsmentioning
confidence: 99%
“…Notably, the resulting FOXP3-expressing T cells can either exert suppressive functions [9,11,13,15,18] or not [12,14,[16][17][18]. Stimulation via TCR of Teff cells, which results in transient FOXP3 expression [16,17], does not confer suppressive activity.…”
Section: Foxp3 Expression In T Cellsmentioning
confidence: 99%
“…We and others have recently shown that cells endowed with regulatory capacity comparable to that of naturally occurring Tregs might be obtained upon activation of naive T cells in the presence of the cytokine TGF-b 8,9 . This protocol describes the methods used in these papers in more detail.…”
Section: Introductionmentioning
confidence: 99%